Applications of silver nanocatalysts for low-temperature oxidation of carbon monoxide - Dey S.; Dhal G.C. (My University, 2025)
Silver (Ag) is the best catalyst for many catalytic oxidation reactions. It is highly active for total oxidation of carbon monoxide (CO) at a lower temperature. The performance of silver catalysts depending upon their structure, surface active sites, and various Ag-O interactions. The other factors effects on the silver catalysts performances are synthesis method, treatment and reaction conditions and sizes of various Ag nanoparticles. The role of various silver species Ag0/Ag+ has examined and Ag0 as an active species originated to increases the catalytic activity at ambient conditions. The nano-sized Ag catalysts have concerned much interest because of their distinctive catalytic activity for different reactions. The silver catalysts highly dispersed over various support would be constructive for the best activity in CO oxidation at low temperatures. The particle size has certain effects on the catalytic performances of supported Ag catalysts. For active supports, the lattice oxygen presence in the support and electron transform among the silver‐oxygen and transition metals play a major role in the catalytic process. There are huge research articles are present on this matter, but very few numbers of review papers are available on this issue. So this is a gap fulfilled by this manuscript. © 2019 Elsevier B.V.